Investigation About How to Promote Foreign Language Learners’ Intercultural Communicative Competence in Higher Education - Wang, Mantong (Trinity College (Dublin, Ireland). School of Education, 2022)
This dissertation aims to investigate foreign language learners’ intercultural communicative competence (ICC) in higher education. The study aims to explore existing research outcome on the variables that have impact on ICC as well as ways of assessing and promoting it. In the first chapter of the dissertation, the broad research background and the structure of the dissertation are shown. Nowadays, the objective of foreign language education is no longer only to develop learners' language competence and cultivate native-like foreign language learners, but also to develop learners' ICC (Byram & Golubeva, 2020). In the second chapter, the concept of interculturality, definitions of ICC as well as theoretical models of ICC are firstly clarified. After clarification of concepts related to ICC, the complexity of ICC assessment, ICC assessment in higher education and the controversy about approaches to assess ICC are presented. After discussion about the topic of ICC assessment, ICC teaching objectives and important considerations regarding ICC-oriented teaching practice with two examples of ways to promote ICC (study abroad and telecollaboration) are clarified. In the final part of chapter 2, evolving approaches to foreign language teaching are introduced. In the third chapter, the research design and methodology informing the study are presented. The research procedure mainly includes eight steps: 1) formulate the problem, 2) develop and validate the review protocol, 3) search literature, 4) screen for inclusion, 5) assess quality, 6) extract data, 7) analyze and synthesize the data, 8) report findings. The study adopts the systematic literature review as the data collection method and narrative synthesis as the data analysis method. The database Ebsco is utilized for searching literature. In the fourth and fifth chapter, data collected from chapter 3 is analyzed, reported and further interpreted through adopting the method of narrative synthesis. Six key findings for answering 3 research questions are proposed: 1) there are confounding variables impacting ICC, 2) four variables having salient impact on ICC are attitude towards other cultures, ethnocentrism, sensation seeking and motivation to engage in intercultural communication, 3) the multi-method and multi-perspective way for assessing ICC is suggested, 4)four outstanding assessment instruments suggested for assessing ICC are questionnaire, reflection paper, paper-test and role-play, 5) the multi-strategy way for promoting ICC is suggested, 6) four outstanding strategies suggested for promoting ICC are explicit instruction, authentic task of intercultural communication, reflection paper and watching film clips. In the final chapter, main arguments are synthesized. Moreover, recommendations, limitations of the study and implications for future research are proposed.
Keywords: Language Education; Education